MENINGKATKAN KEMAMPUAN ‘GRAMMAR’ MAHASISWA JURUSAN BAHASA INGGRIS FBS UNP SECARA LISAN DAN TULISAN - Isyam, Amri; Zainil, Yetty (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2010)
English Department Students as EFL learners must be able to use correct grammar of English well either in oral or written form; nevertheless, based on a prelimenary observation many of the English Department Students of Faculty of Languages, Letters and Arts of State University of Padang committed grammatical deviations when they communicated in English. This article aims at describing the action research about using OHP/LCDP, Role Plays/Language Games, and written exercises as the efforts to improve Grammatical Ability of the English Department Students. The research was carried out in two cycles, and the subjects were a class of education program consisting of thirty students, who were taking Structure 2 at that time. The findings of the research showed that using OHP/LCDP as media of teaching, Role Play/Language Games as oral exercises, and asking the subjects to do two kinds of written exercises (homework from their handbook as usual and their own sentences/paragraphs as assignments) in teaching Structure 2 communicatively improved the students’ grammatical ability either in oral or written forms much more significantly. Their grammatically-oral ability increased by 14.5 points/73.5% (from 21.8 to 36.3) whereas their grammatically-written ability increased by 13.1 points/82.3% (from 19.1 to 32.2) on the average. Thus, the research questions were answered positively, and the hyphotheses were proven.